FLEAS OF CTENOCEPHALIDES (SIPHONOPTERA: PULICIDAE) ON CAT AND DOG IN HOME ENVIRONMENT, PALEMBANG CITY - Astrid Sri Wahyuni Sumah; Ririn Puspitasari; Delsan Ahmad Forwanto (Jurnal Kedokteran Hewan, 2019)
Dogs and cats are often kept as pets, thus they stay close to humans. Parasitic/zoonotic diseases in humans were often caused by ectoparasite in cats and dogs. This study aimed to determine the morphological differences between cat fleas and dog fleas and the prevalence of cats and dogs infested by fleas around the home environment in Ilir Barat 1 District, Palembang City. The method used was descriptive exploratory method with field observation techniques and specimen collection. The study was conducted in November - December 2018 in five Sub-districts, (Bukit Lama, Bukit Baru, Lorok Pakjo, Demang Lebar Daun, and 26 Ilir 1). The results showed that cat fleas (Ctenocephalides felis) and dog fleas (Ctenocephalides canis) had different color and some morphological differences, such as the shape of the head, the number of spines in the genal comb, the number of notches in the tibia, and the number of seta in the metapisternum. The highest prevalence of fleas infestation in cats was in Bukit Lama and 26 Ilir 1 (33.3%), while the highest prevalence of infestation in dogs was in Demang Lebar Daun Village (36.6%). Only in Lorok Pakjo Sub-district that no dog fleas infesting dogs are found. __________________________________________________________